UNTANGLING BINARIES: WHERE CANADA SITS IN THE “21st CENTURY DEBATE” - Gallagher, Tiffany; Rowsell, Jennifer (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2017)
This article examines the extent to which the competencies of the 21st century learner are reflected in the learning outcomes within the English language arts curriculum standards documents for the Canadian provinces. Manifest summative content analysis was used to code learning outcomes in accordance with themes derived from the competencies of 21st century learners. For all provinces, there were few learning outcomes that required students to use digital resources to access information or create knowledge / solutions; there were no learning outcomes related to competencies in the context of core subjects or using social media to communicate and learn. Espoused learning pedagogies need to be galvanized into English language arts curriculum standards that are consistent with 21st century and digital literacy learning competencies.